Pelatihan Pengolahan Jajanan Sehat berbasis Rumpul Laut dalam rangka Pencegahan Masalah Gizi Buruk di Kabupaten Kupang: Training on Processing Seaweed-based Healthy Snacks in the Context of Preventing Malnutrition Problems in Kupang Regency - Pellokila, Marthen Robinson; Picauly, Intje; Marni, Marni; Talahatu, Anna Henny (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Processed snacks are served in many places, in various types, and are very popular with various groups, including children under five. The snacks in question are traditional and manufactured drinks and processed foods. This service activity was carried out to increase the knowledge and skills of family mothers in choosing and processing healthy snacks for family members, including toddlers, in Tablolong Village, West Kupang District, Kupang Regency, on July 29, 2023, with 50 family mothers participating using the